Form and function of the dewa sembilan (nine deities dance) dance in wedding ceremonies - Rensi Febriyentika; Indrayuda Indrayuda (Lentera Negeri, 2026)
This study will provide a basis to know what local factors help to maintain a performing art tradition against cultural decay. The study follows ethnographic qualitative research, which data were collected by conducting participant observation, in-depth interview with 7 individuals selected by purposive and snowball sampling methods (i.e. traditional arts custodian, dancers-trainers, musicians, and community/government figures), and documentary techniques (taking pictures, videos and recording of archival records). Data interpretation was done through three steps: data reduction, data display, and concluding drawing while credibility was guaranteed through triangulating data from different sources and methods. Research results showed that DanceDewa Sembilan performance structure comprises bridal procession, welcoming DancePersembahan, central performance itself, thirteen main physical patterns, six connecting movements, a live traditional music performance, a troupe of nine unmarried female dancers, a specific face paint and costume, and three objects that are regarded as symbols (plates, candles, and robes). It also functions in four ways: (i) religious, (ii) social, (iii) entertainment, and (4) symbolic. Interestingly, unlike how other forms of Sumatran wedding dances have secularized, the core roles of DanceDewa Sembilan haven't gone away from their sacred dimension. The changes have only been superficial (i.e. the length of the performance, the location where it is performed, and some details in costumes). Such steadfastness is maintained because the community follows their customary law and the fact that performing the dance is reserved solely for women who haven't undergone the wedding ceremony yet. Therefore, this study serves as a real life case showing how a wedding dance that carries religious elements can be kept functional despite pressures of modern life and provides a documentation tool for cultural preservation and also a comparative case study for further research in the field of dances of intangible cultural heritage in Sumatra.